PENAMBAHAN BUAH NANGKA (Artocarpus heterophyllus) DALAM PEMBUATAN SELAI ALBEDO SEMANGKA (Citrullus vulgaris Schard) - Asikin, Nurul; Ali, Akhyar; Harun, Noviar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to obtain the albedo ratio of watermelon and jackfruit in making jams, finally can made jams in according to National Standard of Indonesian(SNI). This research used  Complete Randomized Design (CRD) with five treatments and three replications which were followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research included  PS1 (90% albedo watermelon: 10% meat jackfruit), PS2 (80% albedo watermelon: 20% meat jackfruit), PS3 (70% albedo watermelon: 30% meat jackfruit), PS4 (60% watermelon albedo: 40% meat jackfruit) and PS5 (50% albedo watermelon: 50% meat jackfruit). The results of research showed that the ratio of albedo watermelon and gave jackfruit significantly effect on water content, pectin content, fiber content, total dissolved solids, assessment of sensory of the color,  flavour, texture descriptively as well as colour, texture and overall assessment by hedonic yet no real effect on the flavour of jam in hedonic. The best formulation Jams was  PS4 with  total dissolved solids 67.87˚brix, fiber content 2.01%, water content of 33.46%, pectin content 0.90%.Organoleptic scores of PS4 were 4.00 (like) colour, 3.73 (like) flavour, 3.86 (like) taste, 3.56 (like) texture and 2.12 (like) overall. Keywords: albedo watermelon, jackfruit, jam.